Konsep Dasar Metabolisme Tubuh, Metabolisme Karbohidrat, Protein, Lemak, Mineral Elektrolit, dan Vitamin - Eka Yolanda Putri; Evans Tiandra Tenoyo; Farras Fatikhatul Al Mumtazzah; Frida Nur Wahidah; Hadjar Binar Panggalih; Jihan Aulia Roiska; Liss Dyah Dewi Arini (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This review article discusses the principles and processes of carbohydrate, lipid, protein, and nucleic acid metabolism in organisms. The literature review presented in this article is sourced from scientific journals and accredited books that are relevant. The metabolic pathways of carbohydrates, lipids, proteins, and nucleic acids consist of three types of pathways, namely catabolic, anabolic, and amphibolic. These pathways generally occur in the mitochondria through the Krebs cycle. The catabolism of proteins, carbohydrates, and fats can produce derivatives such as amino acids, glucose, glycerol, and fatty acids, which can be converted into energy or energy reserves for cell growth and development processes. Conversely, anabolic processes can utilize macromolecule derivatives (amino acids, glucose, fructose, fatty acids) to form macromolecules (proteins, carbohydrates, and lipids). Carbohydrate metabolism specifically involves glycolysis, glycogenesis, and gluconeogenesis, while lipid metabolism occurs through the acetyl-CoA process.